The Role of the Security Council in Confronting Epidemics: An Analytical Study in Light of the Emerging Coronavirus Crisis - Emar , Omar Mahmoud (Dirasat: Shari’a and Law Sciences, 2021)
This research sheds light on the role of the Security Council in confronting global health pandemics as threats to international peace and security. It also addresses including these threats within the scope of Chapter VII of the United Nations Charter as a precedent practiced by the Security Council due to the spread of the Ebola epidemic in West Africa. However, despite the importance being given to global epidemics, the Council was unable to make any decision to combat the Coronavirus pandemic. Instead of being present and united in light of this pandemic, the Council remained absent due to mutual accusations between the United States of America and China about the origin of the new epidemic, Coronavirus (COVID-19). The study followed the descriptive and analytical approach by analyzing international law and its relationship to peacekeeping and the protection of Public Health and analyzing the reasons for the failure of the Security Council in the fight against the coronavirus pandemic. The study showed the failure of the Security Council to convene to combat this epidemic and also showed the weakness and limited powers of the World Health Organization in making binding decisions for countries in this regard. The study recommended the need to study this topic and analyze it in depth to identify the reasons for the failure of the international community to respond to this pandemic by putting forward new ideas.